Design and Construction of a Web-Based Business Incubator Selection and Evaluation System for Yarsi University - Suhaeri; Aisyah Rutul Jummah; Harry Budiantoro (Informatics and Software Engineering, 2026)
The research problem, namely the challenges faced by startups and business incubators in developing entrepreneurial activities within universities, is relevant and supports the motivation for developing the proposed system. The research method, including the use of development research, observation, literature review, and the prototyping approach, is also briefly explained. However, although the abstract covers the main components of the study, the description of the research results is still presented in a general manner. It does not sufficiently explain the specific achievements of the developed system. The author is advised to provide more detailed information on the system's evaluation results, particularly the outcomes from usability or user experience testing. For example, the abstract could specify which UEQ (User Experience Questionnaire) dimensions achieved the highest evaluation scores and explain their implications for the usability, effectiveness, or acceptance of the proposed system. Presenting more specific quantitative results would strengthen the evidence of the system's performance and make the research contribution clearer to readers. Furthermore, several statements in the abstract, such as improvements in innovation and creativity and the development of successful startups, remain broad and appear to be assumptions rather than conclusions directly supported by the research findings. Since the study primarily focuses on the design, development, and evaluation of a web-based business incubator selection and evaluation system, the abstract should emphasize the outcomes achieved through the system's implementation and testing. The conclusion should be more closely connected to the evaluation results to ensure consistency between the research objectives, methodology, findings, and final claims.